The sky was ours - Fassler, Joe (Penguin Books, 2024)
"From prizewinning writer Joe Fassler comes a brilliant modern reimagining of the myth of Daedalus and Icarus as a story of obsession, longing, and the radical pursuit of utopia. It's 2005, and 24-year-old Jane is miserable. Overworked, buried in debt, she senses the life she wanted slipping away--while the world around her veers badly off course, hurtling toward economic and ecological collapse. She wants to find something better. But she has no idea where to start. In a sudden and unprecedented burst of rebellion, Jane decides to abandon everything she knows, leaving behind her relationships and responsibilities to go on the road. That's how she meets Barry, a brilliant and charismatic recluse living on an isolated homestead near New York's Canadian border. For years, in secret, Barry's chased an unlikely obsession: to build a pair of wings humans can fly in, with designs inspired by an obscure precursor to the Wright Brothers. It's no mere hobby. He's convinced his dream of flight will spark a revolution, delivering us from the degradation of modern capitalism and the climate chaos that awaits us. Jane is captivated by Barry's radical vision, even as his experiments become more dangerous. But she's equally drawn to the enigmatic Ike, Barry's gentle, thoughtful son, who's known no other reality--and who only wants to keep his father alive, tethered to ground and to reason. So begins an inventive, dazzlingly beautiful story about the human desire for transcendence--our longing to escape the mundane and glide into a euphoric future. Inspired by the myth of Daedalus and Icarus, The Sky Was Ours is a powerful and imaginative debut that explores the question: If you had access to technology that allowed you to escape the confines of your life, would you use it? And if Barry's wings really could change the world, would that be freedom?"--